Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# Show that:$\cot \left( {A + {{15}^0}} \right) - \tan \left( {A - {{15}^0}} \right) = \dfrac{{4\cos 2A}}{{1 + 2\sin 2A}}$

Last updated date: 07th Aug 2024
Total views: 457.8k
Views today: 4.57k
Verified
457.8k+ views
Hint – In this question apply some basic properties of trigonometric identities such as $2\cos C\cos D = \cos \left( {C + D} \right) + \cos \left( {C - D} \right),$$\cot \theta = \dfrac{{\cos \theta }}{{\sin \theta }},{\text{ }}\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$ to reach the solution of the question.

Given equation is
$\cot \left( {A + {{15}^0}} \right) - \tan \left( {A - {{15}^0}} \right) = \dfrac{{4\cos 2A}}{{1 + \sin 2A}}$
Consider L.H.S
$= \cot \left( {A + {{15}^0}} \right) - \tan \left( {A - {{15}^0}} \right)$
As we know $\cot \theta = \dfrac{{\cos \theta }}{{\sin \theta }},{\text{ }}\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$ , so apply these properties in the above equation we have,
$= \dfrac{{\cos \left( {A + {{15}^0}} \right)}}{{\sin \left( {A + {{15}^0}} \right)}} - \dfrac{{\sin \left( {A - {{15}^0}} \right)}}{{\cos \left( {A - {{15}^0}} \right)}} = \dfrac{{\cos \left( {A + {{15}^0}} \right)\cos \left( {A - {{15}^0}} \right) - \sin \left( {A + {{15}^0}} \right)\sin \left( {A - {{15}^0}} \right)}}{{\cos \left( {A - {{15}^0}} \right)\sin \left( {A + {{15}^0}} \right)}}$
Now multiply and divide by 2 in above equation we have
$= \dfrac{{2\cos \left( {A + {{15}^0}} \right)\cos \left( {A - {{15}^0}} \right) - 2\sin \left( {A + {{15}^0}} \right)\sin \left( {A - {{15}^0}} \right)}}{{2\cos \left( {A - {{15}^0}} \right)\sin \left( {A + {{15}^0}} \right)}}$
Now we all know that
$2\cos C\cos D = \cos \left( {C + D} \right) + \cos \left( {C - D} \right), \\ 2\sin C\sin D = \cos \left( {C - D} \right) - \cos \left( {C + D} \right){\text{ and}} \\ 2\cos C\sin D = \sin \left( {C + D} \right) - \sin \left( {C - D} \right) \\$
So, apply these properties in above equation we have,
$= \dfrac{{\cos \left( {2A} \right) + \cos \left( {{{30}^0}} \right) - \left( {\cos \left( {{{30}^0}} \right) - \cos \left( {2{A^0}} \right)} \right)}}{{\sin \left( {2A} \right) - \sin \left( { - {{30}^0}} \right)}}$
Now as we know that $\sin \left( { - \theta } \right) = - \sin \theta$ , so apply this property in the above equation we have,
$= \dfrac{{2\cos 2A}}{{\sin \left( {2A} \right) + \sin \left( {{{30}^0}} \right)}}$
Now we all know that $\sin {30^0} = \dfrac{1}{2}$
$= \cot \left( {A + {{15}^0}} \right) - \tan \left( {A - {{15}^0}} \right) = = \dfrac{{2\cos 2A}}{{\sin \left( {2A} \right) + \dfrac{1}{2}}} = \dfrac{{4\cos 2A}}{{2\sin 2A + 1}}$
= R.H.S
Hence Proved

Note – In such types of questions the key concept we have to remember is that always recall all the properties of trigonometric identities which is all stated above then using these properties simplify the L.H.S part of the given equation we will get the required R.H.S part of the equation.